A Theoretical Analysis of the Relationship Between University Teachers’ Positive Leadership and Students’ Learning Engagement in Guizhou Province - Yang, Zhiyuan; Anuar, Aimi Binti (Journal of Theory and Practice in Education and Innovation, 2025)
Student learning engagement is a key area in higher education quality research, particularly within private universities. In these institutions, the level of student engagement significantly influences both institutional development and the quality of talent cultivation. As important contributors to national human capital, private universities graduate large numbers of students each year. Enhancing the learning engagement of education majors in these institutions is essential to fostering their comprehensive growth and personal development. Moreover, improving student engagement can elevate the overall quality of talent training and institutional performance. Focusing on this issue thus contributes meaningfully to the high-quality development of China’s higher education system by supporting a stronger reserve of qualified professionals.